Organizational trust or beyond appearances - Dromereschi, Maria (Studies and Scientific Researches. Economics Edition, 2010)
People and organizations to whom I am giving life to have an enormous need to trust and be trustworthy. Trust represents a fragile asset who needs to be invested in, which is difficult to obtain and takes time to obtain it, but which can be easily broken. Paradoxically, it is a universal trade currency, world-widely understood and appreciated. The relations based on trust are those which determine a company to grow and create a competitive advantage. Trust generates trust. It is the one that inspires and motivates, requires the preservation of a certain set of values, mainly sincerity, fairness, perseverance and a real preoccupation for meeting the needs of other people.